The computationally guided design of selective targeters of multiple proteins (STaMPs) as a new opportunity for small molecule drug discovery - Kaiser, Thomas M. (Frontiers in Pharmacology, 2025)
Polypharmacology has long been an aspect of drug design for small molecules, and the multi-target pursuit has frequently behaved more akin to divine chance rather than controllable science. Targets unknown or once thought undesirable can often be revealed to be key points of intervention for the positive effects of a drug later in the development of a program or even after its approval. In this review, we look at historical examples of molecular pleiotropism and evaluate how new insights from computational systems biology and small molecule design can aid the rational design of Selective Targeters of Multiple Proteins (STaMPs).